Dynamic market-oriented strategic transformation of university business school in transition countries as institutional response to increased internationalization of business education - Jurše, Milan (Akademija MM, 2009)
The emerging transition to knowledge driven society is accompanied by changing view of knowledge that is increasingly treating as a marketable goods and key source of firms' competitive advantage. In a process of dynamic transformation of European higher education university business schools in Central and Eastern European Countries are confronted with the variety of new strategic challenges characterized by increased competition of new knowledge providers in the market, constant pressure from emerging globalisation of higher education, restrictive budgetary funding practices and politically induced privatisation of higher education as part of government policy of liberalisation of the economy. In the article we elaborate a market-oriented academic management concept as a key tool for successful transformation of traditional university business school into a modern academic business knowledge provider. After analysing key challenges in changing European higher education context we present a requisitely holistic strategic framework for strategic business school management that is based on understanding of complexities of dynamic business education environment and the need for holistic and integrative strategic school's response. It is featured by the creative integration of market and academic sides of strategy into a consistent strategic tool for management of business schools' academic services and processes and aligning them with the requirements of key external stakeholder in a dynamic business education context.
Keywords: Central Europe; Eastern Europe; knowledge; konkurenčnost; management; podjetništvo; poslovna strategija; srednja Evropa; strokovno izobraževanje; tranzicija; visoko šolstvo; vzhodna Evropa; znanje